Double-Docking Technique, an Optimized Process for Intrathoracic Esophagogastrostomy in Robot-Assisted Ivor Lewis Esophagectomy - Wang, Fuqiang; Zhang, Hanlu; Qiu, Guanghao; Wang, Zihao; Li, Zhiyang; Wang, Yun (Frontiers in Surgery, 2022)
Background Though robotic Ivor Lewis esophagectomy has been increasingly applied, intrathoracic esophagogastrostomy is still a technical barrier. In this retrospective study, we introduced a double-docking technique for intrathoracic esophagogastrostomy to optimize surgical exposure and facilitate intrathoracic anastomosis. Moreover, we compared the clinical outcomes between the double-docking technique and anastomosis with a single-docking procedure in robotic Ivor Lewis esophagectomy. Methods From March 2017 to September 2020, the clinical data of 68 patients who underwent robotic Ivor Lewis esophagectomy were reviewed, including 23 patients who underwent the double-docking technique (double-docking group) and 45 patients who underwent single-docking robotic esophagectomy (single-docking group). All patients were diagnosed with esophageal cancer or gastro-esophageal junction by biopsy before surgery. The technical details of the double-docking technique are described in this article. Results There was no difference in the patient demographics data between the two groups. The median surgical time in the double-docking group was slightly shorter than in the classic group without statistical difference (380 vs. 395 min, p = 0.368). In the double-docking group, the median blood loss was 90 mL, the median number of lymph nodes harvested was 17, and the R0 resection rates were 100% (23/23). There were no differences in the surgical outcomes between the two groups. Conclusions Based on our experience, the double-docking technique provides good surgical exposure when fashioning anastomosis, and such a technique does not increase the surgical time. Therefore, we believe that the double-docking technique is a safe and effective method for intrathoracic esophagogastrostomy while providing good exposure and ensuring the convenience and reliability of intrathoracic anastomosis.